The Importance of using Digital Technology in Archiving Temple Murals in Sri Lanka: Case study based on the Southern Coastal Region (Galle District). - Peduruhewa, C.D. (International Conference on the Humanities (ICH), 2017 Faculty of Humanities, University of Kelaniya, Sri Lanka., 2017)
A large number of temple murals belong to Kandyan era in Sri Lanka are being in an endangered stage due to negligence, vandalism, and natural causes such as water seepage, sunlight, insects, bats, soot etc., Many of these temple murals are at a poor level of conservation despite they are in the list of ‘Protected Monuments’ or recognized as National Heritage in Sri Lanka. Moreover, many of the murals located in these temples are not archived in a proper way. The particular situation emerges a rationale to addresses some ways and means of restoring the temple murals that have a historic and artistic significance of Sri Lankan traditional painting with regard to its form, style and techniques applied. Thus, the aim of this paper is to emphasize the significance of using digital technology for the purpose of archiving and preserving the heritage of temple murals. The study is mainly based on fifteen (15) selected temples of the Southern Coastal Region (Galle District) in terms of restoring and archiving them for future purposes. Field visits, museum visits, and literature survey were conducted to identify and obtain the background knowledge on both traditional painting of the particular period and the specific aspects of digital tools and techniques. The results suggest that many of the temple murals that are not properly conserved physically can be archived using available digital technology and can be utilized as informative sources of Sri Lankan temple paintings during the particular period.
Keywords: Preservation of murals; Archiving of murals; Digital Technology; Kandyan era murals; Visual art; Sri Lanka